Modelling O2 and CO2 exchange for development of perforation mediated modifed atmosphere packaging - Fonseca, Susana C. (2011)
Perforation-mediated modi®ed atmosphere packaging relies on the use of macro perforations or tubes to control the O2 and CO2 exchange and create the desired atmosphere inside an otherwise gas-tight package. In this work, the O2 and CO2 exchange through a single tube was studied. Di erent temperatures (5±20°C) and tube dimensions (length from 9 to 17 mm and diameter from 6 to 30 mm) were tested. O2 and CO2 mass transfer coe cients were determined according to a lumped mass transfer capacitance model that yielded a good description of the gas transfer. Temperature in the range tested did not show a signi®cant e ect on the mass transfer coe cients. A multiplicative non-linear equation was found to yield a good prediction of the dependence of the O2 mass transfer coe cient on tube diameter and length. The ratio between the CO2 and O2 mass transfer coe cients, an important parameter in the design of MAP, was 0.81 and none of the factors tested in¯uenced its value.